BALANCED SCORECARD-BASED PERFORMANCE MEASUREMENT IN A REGIONAL HOSPITAL: A STUDY AT PENDAU TAMBU HOSPITAL, DONGGALA - Putri, Amalia; Yamin, Nina Yusnita; Usman, Ernawati; Yuniar, Latifah Sukmawati (Accounting Studies and Tax Journal (COUNT), 2025)
This study evaluates the performance of Pendau Tambu Regional General Hospital (RSUD) using the Balanced Scorecard (BSC) approach. Through a qualitative method, performance is assessed from four perspectives: financial, customer, internal business processes, and learning and growth. Data were collected through interviews with financial staff, patients, patients’ families, nurses, and medical staff, as well as through observation and document analysis. The results indicate efficient and effective financial performance, with an economic ratio of 92.62%, effectiveness of 96.26%, and efficiency of 25.18%. Patient satisfaction was high in medical aspects but lower regarding facilities, there was inefficiency in bed utilization, and human resource development through training remained limited. The implications of this study highlight the need for improvements in bed management, patient facilities, and investment in employee development to enhance overall service quality.